RAD54 N-terminal domain is a DNA sensor that couples ATP hydrolysis with branch migration of Holliday junctions - Nadish Goyal (Nature Portfolio, 2018)
RAD54 stimulates activity of the RAD51 recombinase and catalyzes branch migration of Holliday junctions during DNA repair and recombination. Here the authors show that the N-terminal domain of RAD54 mediates RAD54 oligomerization to promote branch migration, and is the target of phosphorylation that inhibits oligomerization and branch migration but not RAD51 stimulation.